2020
DOI: 10.1109/access.2020.3027782
|View full text |Cite
|
Sign up to set email alerts
|

False Data Injection Attack Detection based on Hilbert-Huang Transform in AC Smart Islands

Abstract: In Smart Island (SI) systems, the operators of power distribution system usually utilize actual-time measurement information as the Advanced Metering Infrastructure (AMI) to have accurate, efficient, advanced control and monitoring. SI system can be vulnerable to complicated information integrity attacks such as False Data Injection Attack (FDIA) on some equipment including sensors and controllers, which can generate misleading operational decision in the system. Today, lack of detailed research in the evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In this work, the input to HHT technique consists of 200 patterns. HHT is completely sensitive to the signal magnitude changing and the Empirical mode decomposition of HHT has been used to compute the spectral energy based on equation (9). The spectral energy of HHT can detect various FDI attack and diagnose changing of loads by FDI attacks.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, the input to HHT technique consists of 200 patterns. HHT is completely sensitive to the signal magnitude changing and the Empirical mode decomposition of HHT has been used to compute the spectral energy based on equation (9). The spectral energy of HHT can detect various FDI attack and diagnose changing of loads by FDI attacks.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…This equation provides the best local fit of a variable phase and amplitude of a trigonometric function up to g(t). However, HHT is only able to generate physically significant outcomes for so-named single-component signals [9]. The below Equation is defined the signal spectral energy:…”
Section: A Huang-hilbert Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…As a common way to destroy the integrity of information, the FDIA is able to interrupt the outcomes of state estimation analysis, therefore misleading the control center's decision. The FDIA was first introduced by Liu in 2009, and the FDIA's point is to conduct coordinated attacks on sensors, falsify specific measurements, and manipulate particular state estimation information [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Some research works on FDIA detection in power systems can be found in [19][20][21][22][23], which widely employ state estimation procedures, for instance, by using Kalman filters in [24], sparse optimization and state forecasting provided in [20], generalized likelihood ratio in [19], Kullback-Leibler distance in [25], Chi-square detector and also similarity matching in [26], and machine learning methods in [27]. But in this paper, FDIA detection has been considered in DC-MGs to detect FDIAs in voltage/current sensors and in the reference amount, actual amounts used in the controllers.…”
Section: Introduction 1backgroundmentioning
confidence: 99%